2000
DOI: 10.1074/jbc.m000633200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms of α5β1 Integrin Activation by Ha-Ras and R-Ras

Abstract: To investigate the possible roles of the Ras/Rho family members in the inside-out signals to activate integrins, we examined the ability of Ras/Rho small GTPases to stimulate avidity of ␣ 5 ␤ 1 (VLA-5) to fibronectin in bone marrow-derived mast cells. We found that both HaRas Val-12 activated VLA-5 through PI 3-kinase p110␦. The mutational effects of the R-Ras effector loop region on adhesion were not correlated with PI 3-kinase activities, consistent with our contention that R-Ras has a distinct pathway to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 49 publications
3
38
1
Order By: Relevance
“…Alternatively, the dierences between HRas and R-Ras could be the result of the activation of distinct isoforms of PI 3-kinase by these two proteins. In support of this hypothesis, recent studies have demonstrated that dierent isoforms of PI 3-kinase couple to H-Ras with dierent binding speci®cities (Kinashi et al, 2000). Thus, eector loop mutations in R-Ras disrupt coupling to PI 3-kinase in a manner distinct from the eects of similar mutations in H-Ras.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Alternatively, the dierences between HRas and R-Ras could be the result of the activation of distinct isoforms of PI 3-kinase by these two proteins. In support of this hypothesis, recent studies have demonstrated that dierent isoforms of PI 3-kinase couple to H-Ras with dierent binding speci®cities (Kinashi et al, 2000). Thus, eector loop mutations in R-Ras disrupt coupling to PI 3-kinase in a manner distinct from the eects of similar mutations in H-Ras.…”
Section: Discussionmentioning
confidence: 59%
“…Thus far, H-Ras has been shown to suppress integrin activation in Chinese Hamster ovary (CHO) cells via its eector serine/threonine kinase Raf-1 (Hughes et al, 1997) and activated R-Ras can antagonize the Ras/Raf suppressor pathway (Sethi et al, 1999). In both myeloid cells and bone marrow derived mast cells activated R-Ras can stimulate both integrin a5b1 activation and a5b1 dependent-adhesion to ®bronectin (Kinashi et al, 2000;Zhang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,42 In those reports, the expression of a constitutively active form of R-Ras resulted in increased cell adhesion to fibronectin and collagen. This was interpreted as an increase in binding affinity of the integrins involved.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Ras V12S35 specifically binds and activates mammalian Raf, but not RalGDS or PI3K Kinashi et al 2000;Pacold et al 2000). Ras V12G37 interacts specifically with RalGDS (resulting in activation of the Ral GTPase; RodriguezViciana et al 1997), PI3K␥ (Pacold et al 2000), and PI3K␦ (Kinashi et al 2000), but not with PI3K␣ or Raf. A third variant, Ras V12C40 , specifically interacts with PI3K␣ but not with PI3K␥, PI3K␦, Raf, or RalGDS.…”
Section: V12 Effector Loop Mutants Activate Different Effector Pathwaysmentioning
confidence: 99%